A case study of the issues and concerns of female users of a unisex restroom in a coffee shop - Mojica, Kaithleen Ireen L.; Quevedo, Ma. Teresa P. (2009.)
The study aimed to identify the design related issues and concerns of female users of a unisex restroom in a coffee shop. Survey was used to determine the activities, opinions, and feelings of the respondents in relation to the use of a unisex restroom. The researcher also conducted an observation to monitor how long each female user was inside the restroom. An interview with the management was performed to know more about the flow of customers in the coffee shop. Lastly, observation and documentation of the restroom were done to record the physical conditions of the space. Purposive sampling was used for the survey based on the criteria set by the researcher. Fifty females comprised the respondents of the study. Questionnaires, observation guides, pencil, paper, tape measure, timer, and camera were the instruments of the study. Result showed that 39 out of 50 female respondents preferred separate restrooms for males and females. Twenty-four respondents thought that sharing a restroom was "a little gross but fine" while 18 found it "disgusting". Male practices in the restroom, hygiene, and health issues were cited as reasons for these reactions. Urinating and hand washing were the prime activities of the respondents in the restroom, while grooming was secondary. Although the restroom provided the amenities that addressed the respondents' priorities, they were still bothered with the lack of provisions for bags and purses, hand dryer, and tissue paper holder, and the small space. In conclusion, the unisex restroom under study was not able to fulfill all of the needs and priorities of the female respondents sufficiently. As far as the respondents are concerned, sharing a restroom with the opposite sex was tolerable but no ideal.
Thesis (BS Interior Design)--University of the Philippines Diliman.
Keywords: Restrooms -- Philippines